2020
DOI: 10.1167/tvst.9.7.50
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Rates of Progression of Macular OCT Measures in Glaucoma

Abstract: The purpose of this study was to compare rates of change of various macular thickness measures and evaluate the influence of baseline damage on macular rates of change. Methods: One hundred twelve eyes (112 patients) with ≥ 2 years of follow-up and ≥ 5 macular optical coherence tomography (OCT) images and 10-2 visual field (VF) tests were included. OCT measures of interests were full macular thickness (FMT), ganglion cell complex (GCC), ganglion cell/inner plexiform layer (GCIPL), ganglion cell layer (GCL), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 36 publications
1
17
0
2
Order By: Relevance
“…Therefore, we kept as much as possible of valid data to provide accurate results from the model. We recently reported that GCC is potentially the optimal inner macular parameter for detection of glaucoma progression across the spectrum of glaucoma severity, 4,20 and thus we used GCC as the macular outcome of interest for this study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, we kept as much as possible of valid data to provide accurate results from the model. We recently reported that GCC is potentially the optimal inner macular parameter for detection of glaucoma progression across the spectrum of glaucoma severity, 4,20 and thus we used GCC as the macular outcome of interest for this study.…”
Section: Discussionmentioning
confidence: 99%
“…Superpixels or even clusters of superpixels across the macula are correlated, with the correlation being a function of physical or physiologic distance between the superpixels. 20 We analyzed data for each superpixel separately. This made the modeling easier, at a cost of not allowing us to borrow strength from neighboring superpixels to better estimate trends at each superpixel and preventing us from making joint statements about individual trends across superpixels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations